DIGITAL MODULE DEVELOPMENT SCL-BASED FOR MATHEMATICS STUDY APPLICABLE IN NAUTICA DEPARTMENT - Arie Puji Astuti; Meini Sondang; Nurmida Chaterine Sitompul (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2020)
This study aims to make the development product in the form of an applied mathematics digital module that is used as teaching material for cadets at the Nautics Department at the Surabaya Shipping Polytechnic. This development product includes teaching material and simulations that can be executed through the links available in teaching materials to facilitate understanding the material. The research method uses the waterfall development model with 5 (five) stages, namely needs analysis, design and implementation, testing, product release, product maintenance. Development products are tested to content, media experts, and development design experts to obtain product feasibility. The development products were then tested in small groups (6 cadets) and large groups (26 cadets) and allied teacher assessments. The average results of the feasibility assessment by experts amounted to 79.2% or very well qualified. The product feasibility assessment from the small group test was 83.6%, while the product feasibility assessment from the large group test was 85.7%. The scores of allied lecturers were 93.3%. This digital module of applied mathematics is effective in learning and there are simulations that help cadets understand the material